2022
DOI: 10.3389/fonc.2022.862564
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related miRNA-195-5p Inhibits the Progression of Lung Adenocarcinoma by Targeting Polypyrimidine Tract-Binding Protein 1

Abstract: PurposeLung adenocarcinoma (LUAD) is the most common type of cancer and the leading cause of cancer-related death worldwide, resulting in a huge economic and social burden. MiRNA-195-5p plays crucial roles in the initiation and progression of cancer. However, the significance of the miRNA-195-5p/polypyrimidine tract-binding protein 1 (miRNA-195-5p/PTBP1) axis in the progression of lung adenocarcinoma (LUAD) remains unclear.MethodsData were collected from The Cancer Genome Atlas (TCGA) and Gene Expression Omnib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The results showed that mir-195-5p had a significant inhibitory effect on the proliferation, cloning, and invasion of tumor cells, consistent with the findings that mir-195-5p inhibited the progression of osteosarcoma and breast cancer by targeting FASN summarized by Yu et al [ 64 ]. In addition, although Duan et al demonstrated that mir-195-5p is inversely linked with immune cell infiltration in lung adenocarcinoma [ 65 ], the precise molecular mechanism has not been investigated. Dobosz et al showed that miRNAs can also be involved in tumor-cell–immune-cell interactions by regulating post-transcriptional regulation of immune checkpoint genes [ 66 ], which made mir-195-5p development as a small molecule drug more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that mir-195-5p had a significant inhibitory effect on the proliferation, cloning, and invasion of tumor cells, consistent with the findings that mir-195-5p inhibited the progression of osteosarcoma and breast cancer by targeting FASN summarized by Yu et al [ 64 ]. In addition, although Duan et al demonstrated that mir-195-5p is inversely linked with immune cell infiltration in lung adenocarcinoma [ 65 ], the precise molecular mechanism has not been investigated. Dobosz et al showed that miRNAs can also be involved in tumor-cell–immune-cell interactions by regulating post-transcriptional regulation of immune checkpoint genes [ 66 ], which made mir-195-5p development as a small molecule drug more challenging.…”
Section: Discussionmentioning
confidence: 99%